2002
DOI: 10.1016/s0969-2126(02)00829-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 4 Is a Transcription Factor that Constitutively Binds Fatty Acids

Abstract: The 2.7 A X-ray crystal structure of the HNF4gamma ligand binding domain (LBD) revealed the presence of a fatty acid within the pocket, with the AF2 helix in a conformation characteristic of a transcriptionally active nuclear receptor. GC/MS and NMR analysis of chloroform/methanol extracts from purified HNF4alpha and HNF4gamma LBDs identified mixtures of saturated and cis-monounsaturated C14-18 fatty acids. The purified HNF4 LBDs interacted with nuclear receptor coactivators, and both HNF4 subtypes show high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
242
1
6

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(263 citation statements)
references
References 44 publications
(6 reference statements)
11
242
1
6
Order By: Relevance
“…ligandindependent) nuclear receptor. Structural studies have revealed the presence of a previously unrecognized fatty acid docked in the ligand-binding domain of HNF4α [31,32], consistent with the finding that fatty acids regulate HNF4α-dependent gene expression [52,53]. Fatty acids may also modulate STAT5 activity [54,55].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…ligandindependent) nuclear receptor. Structural studies have revealed the presence of a previously unrecognized fatty acid docked in the ligand-binding domain of HNF4α [31,32], consistent with the finding that fatty acids regulate HNF4α-dependent gene expression [52,53]. Fatty acids may also modulate STAT5 activity [54,55].…”
Section: Discussionsupporting
confidence: 70%
“…Structural studies have revealed that fatty acids serve as endogenous ligands of HNF4α [31,32]. Moreover, short-chain fatty acids, such as butyrate, can enhance GH-induced STAT5b activity [33].…”
Section: Effect Of a Short-chain Fatty Acid On Hnf4α Inhibitory Effectsmentioning
confidence: 99%
“…It is tempting to speculate that such up-regulation might be achieved through increased association of MDT-15 with the NHR-49-LBD, perhaps driven by binding of the receptor to a hormone-like small molecule(s) whose levels fluctuate in response to food availability. It may be significant in this regard that specific FAs associate with the LBD of HNF4␣ (Hertz et al 1998;Wisely et al 2002). Thus, nutrient availability may signal to NHR-49:MDT-15 regulatory complexes to modulate a sector of metabolic gene expression.…”
Section: Mdt-15 Is An Nhr-49 Coregulator In Vivomentioning
confidence: 99%
“…1) (8,(11)(12)(13)(14)(15)(16). The molecular basis for this constitutive activity remains to be determined but may include ligand-based mechanisms involving dietary or endogenous long chain fatty acids (LCFA) (17,18), endogenously synthesized coenzyme A (CoA) thioesters of long chain fatty acids (LCFA-CoAs) (8,11,14,19), and/or the F-domain itself functioning as a modulator (16).…”
mentioning
confidence: 99%